Mercury Catalyzed the Hydrolysis of Quinalphos - Abdelhamid Esbata1*, Erwin Buncel2, Gary VanLoon2 (AlQalam Journal of Medical and Applied Sciences, 2020)
Hydrolysis of the organophosphorothioate compound, quinalphos (Q, O,O-diethyl O-quinoxaline-2-yl phosphorothioate) in the presence of Hg2+ was investigated at 25oC and pH 4.0, 7.0 and 10.0 using HPLC with UV detection. The hydrolysis products were 2-hydroxyquinoxaline (HQ) and O,O-diethyl phosphorothioic acid (PA). The kinetic results show clearly that mercury ion catalyzed the hydrolysis of Q, as the catalytic rate increased by presence of Hg2+. The maximum kobs was observed at the lowest pH value (pH 4.0). In the second part of this work, Electrospray ionization mass spectrometry (ESI-MS) technique was used to study how Hg2+ coordinates the substrate (Q) in ways that accelerate hydrolysis. [(PA)2 + Na + Hg]+ complex was formed; this indicates that the binding takes place between Hg2+ and the S atom.